Prevalence of Arboviruses in Northeast Capitals (Research, Society and Development, 2022)
Objective: analyze the distribution profile of the prevalence of arboviruses in northeastern capitals. Methods: This is a review article, the data used were secondary, available on the website of the Department of Informatics of the Unified Health System (DATASUS) through TABNET, between the years 2017 to 2020, collected in the period of September 2021. Results: The incidence and prevalence of Chikungunya and Zika cases, was higher in northeastern capitals, due to climatic factors, on the other hand Dengue had a higher prevalence in the Southeast, due to its large urban centers, in addition there was a higher incidence of cases in women, as men seek for less medical care. Regarding the expenses resulting from these diseases, they generate considerable consequences for the SUS and consequently for the country. Conclusion: Public policy programs for the control of arboviruses are effective, however it is still necessary to apply them more effectively, in order to promote the reduction of new cases.